Analisis Sistem Rekrutmen Dalam Upaya Meningkatkan Kinerja Karyawan Pada Tirta Tarum PDAM Karawang - Selvi Pebriyanti; Uus MD Fadli (Yayasan Daarul Huda Kruengmane, 2023)
Recruitment of employees is one of the important factors in a company. Recruitment is needed to find Human Resources (HR) to fill a job in the company. In the recruitment process, companies should be selective to avoid mistakes in recruiting employees. Writing Method In writing this report the writer uses a descriptive writing method, namely writing the results of work practices by describing or describing the employee recruitment process at PDAM Karawang. In describing the employee recruitment process at PDAM Karawang, a flow chart is made to show the stages in the employee recruitment process. Data Collection Techniques with Library Studies, Field Studies, and Interviews.